Menciptakan Suasana Perjumpaan Antar-Agama: Refleksi Filosofis Etika Global Hans Küng : Creating an Inter-Religious Meeting Atmosphere: Philosophical Reflections on Global Ethics Hans Küng - Marz Wera (Sekolah Tinggi Teologi Satyabhakti, Malang)
Indonesia faces the problem of differences for many year ago until now. Even though, Pancasila symbolizes the unity but mostly in religious relationship have a cliff between ''us’’ and ‘’them’’ for many reasons recently. Another problem emerges in area of Religious pluralism, makes the situation more difficult. The reality of religious diversity is isolated by misleading and shallow interpretations. The space for dialogue is insulated by religious formalism and theological claims of truth. The dialogue of agreement, both inclusivism and pluralism, has not been able to knit religious plurality. Traditions, symbols, rituals, ethical dimensions and universal core in religious dialogue as a precondition do not find space. In this context, the author is trying to offer the idea of